Academic Unit Worthy of Example - García Neira, Carlos (Revista Universidad de Guayaquil, 2008)
Upon entering the Faculty of Psychological Sciences of the University of Guayaquil we find an Academic Unit with order, cleanliness, neatness very different from the others, where its floors, walls and classrooms shine like a mirror, an example of organization on the part of the authorities of this Superior Center.by the authorities of this Superior Center.In its interior we find well-kept gardens accompanied by a waterfall that gives it a stately impetus where university students feel very comfortable to study and acquire their knowledge of psychology on a daily basis.We engage in a small dialogue with the first authority of this Center, the Psychologist Gonzalo Flores who gives us to know some aspects, especially the academic resources and the careers that they have until now.
Keywords: Faculty of Psychological Sciences